RESPONSE OF DIFFERENT LEVELS OF NITROGEN AND SPACING ON YIELD AND QUALITY OF CAULIFLOWER GROWN UNDER CENTRAL REGION OF PUNJAB - PAWANDEEP KAUR; S. K. SINGH; MANDEEP KAUR SIDHU (The Bioscan, 2020)
The field experiment was conducted during rabi season of 2018-2019 to find out the response of different levels of nitrogen and spacing on yield and quality of cauliflower. The experiment was carried out under Factorial Randomized Block Design (FRBD) with three replications and twelve treatments with four different levels of nitrogen levels (N0: 0%; N1: 50%; N2: 75% and N3: 100 % ha -1 ) and three different spacing (S1: 45×30 cm; S2: 45×45 cm and S3: 60×45 cm). The result revealed that the maximum fresh weight of curd (833.33 g), dry weight of curd (0.89 g), shelf life (8.07 days), total soluble solids (5.05ºBrix), vitamin A (16.35 mg), vitamin C (68.40 mg) and chlorophyll content in leaves of cauliflower (1.68 mg) were obtained from N 100 S 45×30 . While, maximum curd yield plot -1 (30.03 kg) and ha -1 (326.90 q) were obtained from N 100 S 45×30 . However, maximum net return ( 299443.45) and B: C ratio (3.22) were obtained with 100 % N ha -1 + 45×30 cm. On the basis of results of present investigation, it concluded that treatment T 12 (100 % N ha -1 + 60×45 cm) were found effective in improving the yield and quality of cauliflower.